A Study Of The Level Of Skill Self-Efficacy And Some Aspects Of Attention And Their Relationship To The Skill Of Crushing Hitting (Frontal, Linear And Diagonal) In Volleyball From Sitting For The Disabled, Class F45 - HamadAfatRasheed (International Journal of Psychosocial Rehabilitation, 2020)
To raise the level of performance skills of volleyball players, they play an important role in the competition, so it has become necessary for the coach to have facts and information about the characteristics of the motor performance of the psychological aspects that are difficult to perform. Only get to follow the player’s status and improve his level. It is a volleyball game for the disabled F45 class of games that is characterized by its cup and ease of training in addition to technical development and various tactical skills, including the skill of smashing as well as the skill of the skills they can do. Get direct points for registration. Points and progression, so it is a critical skill in volleyball, Paralympic volleyball sitting game is an F45 class that needs many requirements to achieve technical performance, including physical qualities, skill, and psychological abilities, although there are many manifestations of psychological abilities in ridding the level of effectiveness of subjective skills and attention, which are the most important aspects of achievement (unity, focus, and tactics), and the fishermen who have an active role in implementing the skill of smashing the volleyball. Sitting for the disabled category F45 Hence the importance of the research in studying the level of self-efficacy of the skill and some aspects of attention (acuteness, concentration, deviation) and trying to find out the type of relationship that each of them related to the crushing skill (confrontation, linear and diagonal) in volleyball from sitting to the disabled category